Feasibility and significance of stimulating interscapular muscles using transcutaneous functional electrical stimulation in able-bodied individuals. (30th September 2021) - Kapadia, Naaz; Moineau, Bastien; Marquez-Chin, Melissa; Myers, Matthew; Lon Fok, Kai; Masani, Kei; Marquez-Chin, Cesar; Popovic, Milos R.
Abstract : Objective: The study objective was to assess the feasibility of stimulating the lower trapezius (LT), the upper trapezius (UT) and serratus anterior (SA) muscles along with anterior or middle deltoid, using surface functional electrical stimulation (FES). The secondary aim was to understand the effects of LT, UT, and SA stimulation on maximum arm reach achieved in shoulder flexion and abduction. Design: Single arm interventional study. Setting: Inpatient Rehabilitation Hospital. Participants: Ten healthy volunteers. Intervention: Participants completed 10 trials for each of the 3 conditions in flexion and abduction, i.e . (1) Active voluntary flexion or abduction, (2) FES for anterior deltoid for flexion or middle deltoid for abduction, and (3) FES for LT, UT, and SA along with anterior deltoid for flexion or middle deltoid for abduction. Outcome Measures: Maximum arm reach and percent angle relative to the voluntary movement were computed from motion capture data for each condition. Wilcoxon signed-rank test was used to compare the maximum reach between two FES conditions. Results: The study results showed that all three interscapular muscles can be stimulated using surface FES. Maximum reach in abduction was greater for FES of middle deltoid along with the interscapular muscles (51.77° ± 17.54°) compared to FES for middle deltoid alone (43.76° ± 15.32°; Z = −2.701, P = 0.007). Maximum reach in flexion for FES of anterior deltoid, along with interscapular muscles, was similar to that during FES of anterior deltoid alone. Conclusion: Interscapular muscles can be stimulated using surface FES devices and should be engaged during rehabilitation as appropriate.